Hubungan Kadar Trombosit dan Hematokrit Terhadap Mortalitas Pasien Stroke Iskemik Fase Akut - Pela Meyadsa (Universitas Adiwangsa Jambi, 2025)
Ischemic stroke is a major medical condition with a high mortality rate, particularly during the acute phase. Various factors influence the prognosis and mortality of ischemic stroke patients, including hematological factors such as platelet count and hematocrit levels. This study aims to analyze the relationship between platelet count and hematocrit levels with mortality in acute ischemic stroke patients in the hospital. This study used an observational analytic design with a cross-sectional approach. Data were collected from medical records of patients admitted to the intensive care unit (ICU) and inpatient ward with a diagnosis of acute ischemic stroke between January and December 2025. Platelet count and hematocrit levels were measured on the first day of hospital admission and correlated with 30-day mortality. Statistical analysis was performed using the Chi-Square test to assess the relationship between the independent variables (platelet count and hematocrit levels) and the dependent variable (mortality). The results of the study showed that patients with higher platelet counts and lower hematocrit levels had a significantly higher risk of mortality compared to other groups. These findings suggest that elevated platelet count and low hematocrit levels may serve as important prognostic indicators in predicting mortality in acute ischemic stroke patients. This study provides additional insights into the importance of monitoring hematological factors in the management of acute ischemic stroke patients and could serve as a foundation for developing more targeted therapeutic strategies.